Seroprevalence of Hepatitis E virus in children and adolescents living in urban Bogotá: An explorative cross-sectional study - Fernández Villalobos, Nathalie Verónica; Kessel, Barbora; Torres Páez, Johanna Carolina; Strömpl, Julia; Kerrinnes, Tobias; de la Hoz Restrepo, Fernando Pio; Strengert, Monika; Krause, Gérard (Frontiers in Public Health, 2023)
The majority of Hepatitis E Virus (HEV)-related studies are carried out in adults whereas information about HEV seroprevalence, clinical disease manifestation, molecular epidemiology, and transmission patterns in children is limited. To estimate HEV seroprevalence among scholar children living in an urban setting and to analyze risk factors for an infection, we invited children aged 5–18 years from Bogotá (Colombia) for a cross-sectional survey. We collected self-reported data on demographics, social, clinical, and exposure variables in a structured interview. Venous blood samples were analyzed with two commercially available ELISAs for HEV-specific IgG antibodies. Among the 263 participants, we found three HEV IgG-reactive samples (1.1%) using both assays. We additionally characterized the samples for HEV IgM using a commercially available IgM ELISA and for HEV RNA. Here, we found one IgM-reactive sample, which was also reactive for IgG. In contrast, none of the IgM- and IgG-reactive sera samples showed detectable RNA levels indicating HEV exposure had not been recently. All participants reported access to drinking water and sanitary systems in their households and frequent hand washing routines (76–88%). Eighty percent of children reported no direct contact with pigs, but occasional pork consumption was common (90%). In contrast to the majority of studies performed in Colombian adults, we found a low unadjusted HEV seroprevalence of 1.1% (95% CI: 0.3–3.6%) for both HEV IgG ELISAs in our study population. While the majority of participants reported pork consumption, we speculate in the absence of viral RNA for genotyping in the affected individuals, that existing access to drinking water and sanitary systems within our study group contribute to the low HEV seroprevalence.